Experimental study on cement sheath integrity based on fiber Bragg grating technology. Issue 2 (October 2021) - Chen, Shuo; Jin, Jianzhou; Shen, Jiyun; Guo, Xueli; Ji, Hongfei; Wang, Linlin
Abstract: Fiber Bragg grating (FBG) sensing technology is a new structure monitoring technology. Aiming at the influence of hydration and cyclic casing pressure on cement sheath integrity in real wellbore conditions, firstly, the temperature and strain variation regularities of cement sheath in setting stage are investigated by FBG and a test device for evaluating cement sheath integrity. Then the circumferential strains of cement sheath and casing under cyclic casing pressure are studied. Furthermore, the applicability of FBG technology is verified. The results show that the temperature and strain of cement slurry change rapidly in 5 hours after pouring. In cyclic casing pressure stage, circumferential strains of cement sheath and casing are both tensile strains. In addition, circumferential strain of cement sheath and casing increases with the increase of casing pressure. The FBG sensors have high sensitivity that can reflect the change of casing pressure in time. The FBG technology is a scientific temperature and strain monitoring method for cement sheath. The results of this study are of great significance to the application of FBG technology for cement sheath integrity.